2000
DOI: 10.1097/00005373-200009000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal Hypertension and Abdominal Compartment Syndrome in Burn Patients

Abstract: IAH occurs commonly in major burn patients, and ACS is seen regularly in patients with more than 70% body surface area burns. We recommend bladder pressure measurements after infusion of more than 0.25 L/kg during the acute resuscitation phase and for peak inspiratory pressures greater than 40 cm H2O. Whereas ACS warrants surgical decompression of the abdominal cavity, IAH usually responds to conservative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
1
13

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(159 citation statements)
references
References 13 publications
8
131
1
13
Order By: Relevance
“…Of these, 22 patients (39%) received greater than 250 mL/kg of volume in the first 24 hours. Based on a previous study by Ivy et al 6 this threshold is associated with increased incidence of ACS. Based on our data there was not a detectible association between this group and the incidence of ACS.…”
Section: Resultsmentioning
confidence: 97%
“…Of these, 22 patients (39%) received greater than 250 mL/kg of volume in the first 24 hours. Based on a previous study by Ivy et al 6 this threshold is associated with increased incidence of ACS. Based on our data there was not a detectible association between this group and the incidence of ACS.…”
Section: Resultsmentioning
confidence: 97%
“…20,25 In this project, the incidence of ARDS within the first 5 days of admission was 30% in the preimplementation group and was reduced to 10% in the postimplementation group. After review of data, we found that the preimplementation group had more patients with inhalation injuries (47%) than the postimplementation group (38%), which may have contributed to the improved outcomes.…”
Section: Discussionmentioning
confidence: 86%
“…13 Prevention of abdominal compartment syndrome is a primary goal for burn providers, as abdominal compartment syndrome can lead to decreased pulmonary compliance, cardiac dysfunction, multiorgan dysfunction, and/or organ failure. 8 Ivy and colleagues 25 describe a direct relationship between resuscitation volumes delivered per kilogram and the development of abdominal compartment syndrome, validating the importance of wellorchestrated burn resuscitation. Although multiple factors, including mechanism of injury and systemic inflammatory response, affect the patient's risk for secondary complications, overresuscitation exponentially increases the patient's risk.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The lack of uniformity in definitions for these two entities makes comparisons between different studies difficult [4,5], and has led to a set of proposed definitions [6]. IAH is defined by a sustained or repeated pathological elevation in intraabdominal pressure (IAP) C12 mmHg.…”
Section: Introductionmentioning
confidence: 99%